Biblioteca escolar e EJA: caminhos e descaminhos - Raquel Miranda Vilela (2009)
This research aims to study the role of library in the context of Education for Young and Adults (EJA), owing to that the presence of unlettered subjects and the contradictions of this reality in a society highly centered in graphic symbols, is a motivational aspect and has significant relevance for the accomplishment of this work. The education of those subjects, through the Education of Youths and Adults, represents an opportunity and also an important tool to insert them fully into a Society of the Information. Thereby, thinking the school library in this scenery constitutes a very important dimension for the professionals of the Information Sciences. Thus the research aimed to identify, from the perspective of professionals involved in Youth and Adults (library staff and teachers), the perceptions and roles of the library as well as the strategies used by these professionals in order to meet specific features of the public. The study proposed to contribute to the wider debate on library school, especially in the context of Youth and Adults, to collaborate in the performance of the segments involved, namely the library professionals and teachers. The theoretical analysis was based on the relationship between the library, information and citizenship, as well as the role of school library and its educational function. Rounding out the theoretical framework, we studied the Youth and Adult Education, its historical background, politics and the current situation in the Municipal Schools of Belo Horizonte. In methodological terms, the research used in an integrated quantitative and qualitative dimension, and a questionnaire for the characterization of professors in schools of Belo Horizonte was used. From the questionnaires, criteria were established to determine the subjects of the interviews. The semi-structured interview was conducted with teachers and acting subjects in the school library (librarians, library assistants and teachers in upgrading functional). The research was undertaken in 03 (three) schools in the Municipal Schools of Belo Horizonte. The results showed that the performance of the school library in adult education is still far from ideal, however the data indicate that there are more similarities than disagreements between the perceptions of teachers and library staff. Among the challenges mentioned by the survey, we can mention the need for integration between librarian and teacher, the lack of specific and suitable materials for adult education in the publishing market, as well as the difficulty of time management in their different perspectives. The study concluded that the integration points and time must be studied more thoroughly, since that was important for a more effective librarian action in adult education. We also concluded that the school library is not yet exploited in its full potential, and this can be attributed to lack of specific training for professionals working in schools.